Prevalence of HIV, Syphilis, Hepatitis B and C in pregnant women at a maternity hospital in Salvador - Jacielma de Oliveira Freire; Jaqueline Bohrer Schuch; Mariana Freire de Miranda; Vinícius Serafini Roglio; Helita Tanajura; Ana Gabriela Lima Bispo de Victa; Lisia von Diemen (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to calculate the prevalence and rate per 1,000 live births of sexually transmitted infections (STI) in pregnant women at a public maternity hospital in Salvador. Methods: this descriptive, cross-sectional study retrospectively collected data from compulsory notifications and medical records of pregnant women with STI seen at a maternity hospital in northeastern Brazil between 2014 and 2017 (n = 520). Prevalence and rate per 1,000 live births were estimated for hepatitis B, hepatitis C, HIV, and syphilis. Associations between STI and other clinical and sociodemographic variables were investigated. Results: most pregnant women were born and resided in Salvador, presented a mean age of 26.4 years, self-reported mixed-race and had unplanned pregnancies. Prevalence and rates per 1,000 live births were, respectively: 0.26% and 3.39 for hepatitis B, 0.06% and 0.79 for hepatitis C, 0.47% and 6.23 for HIV, and 2.46% and 32.2 for syphilis. Conclusion: higher prevalence and rates of infection per 1,000 live births were seen at the maternity hospital in northeastern Brazil compared to official data provided by the Brazilian government, notably with regard to HIV and syphilis. The appropriate epidemiological notification of STI, especially in pregnant women, enables the elaboration of effective preventive strategies incorporating specific sociodemographic and clinical characteristics.